Knowledge, Attitude, and Practices (KAPs) on COVID-19 of junior and senior high school students - Ritchelle W. Origenes; Blanca A. Alejandro (University of Muhammadiyah Malang, 2024)
During the COVID-19 pandemic, students faced increased risk of contracting the virus due to the relaxation of health protocols by the Philippine government and the authorization of face-to-face instruction in schools by the Department of Education. There is little data on basic education school students' awareness of COVID-19 in the Philippines, particularly in Cebu City. A cross-sectional descriptive-correlational research design was utilized to determine junior and senior high school students' knowledge, attitudes, and practices regarding COVID-19. In this study, a survey questionnaire was used to compare and attempt to identify relationships between the demographic profile of students and their KAPs regarding COVID-19. This study also investigated the relationships between students' KAPs. JHS and SHS students exhibited outstanding KAPs for COVID-19. Students' demographic characteristics, including grade level and family income, were significantly associated with their KAPs toward the disease. However, their gender was not significantly associated with their KAPs. There was a significant relationship between students' COVID-19 KAPs. It is imperative that the DepEd develop strategies and programs to combat the situation due to pandemic and prepare for similar situations in future. With the aid of curriculum designers, science educators must adapt the science education curriculum to address current and future health concerns.